1981
DOI: 10.1002/1097-0142(19810115)47:2<285::aid-cncr2820470213>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofCorynebacterium parvum on cellular immunity of cancer patients, assayed sequentially over 63 days

Abstract: The immunologic effects of Corynebacterium parvum (2 mg/M2) infused at three-week intervals were determined by 19 sequential assays in each of nine patients with metastatic malignancy. Peripheral blood immunologic profiles were followed for 63 days. No statistical significant changes (P greater than 0.05) occurred in total white cell, lymphocyte, or monocyte counts. Subpopulation assays demonstrated significant increases in E rosetting cells but not in sIg-bearing cells; there was a corresponding significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…parvum, a Gram-positive anaerobic bacillus, is known to be a potent immunological stimulant that can inhibit the growth both of primary and metastatic tumours [9][10][11]. For this reason, it is considered an anti-cancer agent [12].…”
Section: Discussionmentioning
confidence: 99%
“…parvum, a Gram-positive anaerobic bacillus, is known to be a potent immunological stimulant that can inhibit the growth both of primary and metastatic tumours [9][10][11]. For this reason, it is considered an anti-cancer agent [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CP, a strong immunological stimulant, can inhibit growth of primary and metastatic tumors and especially, the progression of cancer pleural fluid [21][22][23][24][25]. However, the major obstacle for further application of CP is attributed to its severe side effects.…”
Section: Discussionmentioning
confidence: 99%